Effect of Sodium-Glucose Cotransporter-2 Inhibitors versus Dipeptidyl Peptidase 4 Inhibitors on Cardiovascular Function in Patients with Type 2 Diabetes Mellitus and Coronary Artery Disease - Lee, Sook Jung; Lee, Kook Hyung; Oh, Hyun Geong; Seo, Hye Ji; Jeong, Soo Jin; Kim, Chong Hwa (Journal of Obesity & Metabolic Syndrome, 2019)
Randomized controlled trials demonstrated lowering risks of cardiovascular events with sodium-glucose cotransporter-2 (SGLT2) inhibitors in patients with type 2 diabetes mellitus (T2DM) and high cardiovascular risk. We analyzed the effects of cardiovascular function on SGLT2 inhibitors compared with dipeptidyl peptidase-4 (DPP4) inhibitors in T2DM with atherosclerotic cardiovascular disease (ASCVD) or heart failure (HF). This is a retrospective, observational, single center study. Data from 89 patients with ASCVD or HF from January 2015 to February 2018 were analyzed regarding the effect of SGLT2 inhibitors and DPP4 inhibitors. Cardiovascular function was assessed by 2-D echocardiography and N-terminal prohormone of brain natriuretic peptide (NT-pro BNP). A total of 89 patients with T2DM were considered in two groups of SGLT2 inhibitors (n=41) and DPP4 inhibitors (n=48). The mean follow-up period was 2 years, with a total of 89 patient-years. Despite no significant change in systolic function, SGLT2 inhibitors improved cardiovascular function, as demonstrated by a reduced left ventricular ejection fraction less than 40%, ratio of mitral peak velocity of early filling velocity to early diastolic mitral annular velocity, ratio of early to late ventricular filling velocities, and NT-pro BNP compared with the DPP4 inhibitor group. SGLT2 inhibitors improve cardiovascular function in T2DM with coronary artery disease compared to DPP4 inhibitors.